FAKTOR YANG MEMENGARUHI KEMISKINAN PETANI DI SEKITAR KAWASAN TAMANNASIONAL LORE LINDU (TNLL)(Kasus di Desa Katu Kecamatan Lore Tengah Kabupaten Poso) FACTORS AFFECTING FARMERS POVERTY AT SURROUNDING NATIONAL GARDEN AREA OF LORE LINDU (TNLL)(Case at Katu Village, Central Lore District, Poso Regency) - Antara, Made (Pembangunan Pedesaan, 2006)
This research aimed at knowing factors influencing poverty level. Sample of location in Katu Village and responder were taken with census method, with number of sample as much as 46 people. Based on result of data analyzed, it was concluded that factors affecting poverty level of farmers were small land use, low formal education, very high dependent level, and lower application of agricultural technology.